The Extended Stability of Cervical Swabs in careHPV™ Collection Medium - Tan, Cheng Siang (Springer Nature, 2020)
Background: The careHPV™ Test is a US FDA approved, CE mark, and WHO prequalified in vitro diagnostic test that is designed to screen for 14 HRHPV genotypes. The careHPV™ Test is the only commercial HPV tests validated to be used in the low resource settings, boasting the economy of processing a maximum of 90 samples per batch and a near point-of-care turnaround time of 3 hours. Cervical swabs stored in the careHPV™ Collection Medium are stable for 30 days when stored between 2–8 °C according to the manufacturer. However, we often had difficulty to consolidate enough samples for a full batch-test within 30 days, especially when screening women living in the low-density villages in the rural Sarawak, Malaysian Borneo.